The difference in radiographic findings in the distal limbs of working Lipizzan horses, used for dressage or driving - Zalig, Valentina; Vengust, Modest; Blagus, Rok; Berner, Dagmar; Sandow, Cole; Hanna, Ashley; Miklavcic, Mitja (Frontiers in Veterinary Science, 2024)
Lameness originating from the distal limb is common in sport horses and can vary depending on the dynamics of movement and the surface, with differences in shoeing exacerbating this variability. Driving horses work primarily on hard surfaces (pavement), whereas dressage horses work primarily on soft surfaces (riding arenas with sand). Driving horses are traditionally shod with small fixed studs made of hard metal, which are attached to the horseshoe at 4 points, while dressage horses are shod with a simple horseshoe. We investigated the hypothesis that there is a difference in the pathological radiographic findings of the distal limbs between driving and dressage horses. The variability in the stable management and training programme was minimised by including horses from the same farm.Twenty horses in a driving training programme and 20 horses in a dressage programme were included in the study. Radiographs of the both front feet were obtained and quantitatively evaluated for radiographic changes by three surgery/diagnostic imaging specialists. Interrater reliability was measured, and multivariate analysis was performed to compare differences in pathological radiographic findings of the distal limbs between the two groups. Kendal's concordance coefficient indicated an agreement among raters (Kw ≠ 0) for all observations. Radiographic signs of degenerative joint disease of the distal interphalangeal joint were more common in the group of driving horses compared to dressage horses. Our hypothesis was confirmed, as there were significant pathological differences between groups in distal articular margin of middle phalanx, joint space narrowing, and irregular joint surface of the middle phalanx.